The Effect of Mating on The Eggs’ Fertility and Fecundity of Helopeltis antonii (Heteroptera: Miridae) - Siswanto,; Rita Muhamad,; Dzolkhifli Omar,; Elna Karmawati, (Tropical Life Sciences Research, 2009)
Helopeltis antonii is the major pest affecting cashew plants in Indonesia and causes potential damage to the plant. The development of the population was influenced by the fecundity and fertility of their eggs. The effect of mating on the eggs’ fecundity and the fertility of H. antonii was studied. Laboratory studies at Wonogiri Estate Service in Ngadirojo District, Wonogiri, Indonesia investigated the sexual maturity, the influence of female to male sex ratio on the females’ fecundity and longevity, and the influence of mating frequency to fecundity and the eggs hatchability of H. antonii. The study reveals that H. antonii females and males are ready to mate when they are two days old. The number of eggs laid and the longevity of the females’ lives were not significantly affected by the sex ratio; however, female to male sex ratios of 2:1 and 1:2 tended to produce a greater number of eggs. The fecundity of the female was not significantly influenced by the number of times the female mated. Unmated females laid fewer eggs than females paired with a mature male. The study shows that females need to mate to produce fertile eggs. Helopeltis antonii merupakan salah satu serangga perosak utama pada pokok gajus (Anacardium occidentale L.) yang boleh menyebabkan kerosakan pada pokok tersebut. Perkembangan populasi H. antonii dipengaruhi oleh kesuburan dan kadar kesuburan telur-telurnya. Pengaruh persenyawaan keatas kesuburan dan kadar kesuburan telur H. antonii telah dikaji. Penyelidikan telah dijalankan di makmal Perkhidmatan ladang daerah Ngadirojo, Wonogiri, Indonesia untuk mengkaji kematangan seksual serangga betina dan jantan, pengaruh nisbah jantina keatas kesuburan telur dan kepanjangan umur betina, dan pengaruh kekerapan persenyawaan keatas kesuburan telur dan penetasan telur. Hasil kajian menunjukkan bahawa betina dan jantan H. antonii bersedia untuk melakukan persenyawaan pada umur dua hari. Jumlah telur yang dikeluarkan dan kepanjangan umur betina tidak dipengaruhi oleh nisbah jantina, tetapi nisbah jantina 2:1 dan 1:2 cenderung menghasilkan lebih banyak telur. Kesuburan betina tidak dipengaruhi oleh jumlah persenyawaan. Betina yang tidak disenyawakan menghasilkan kurang bilangan telur berbanding betina yang berpasangan dengan jantan yang matang. Kajian ini menunjukkan betina memerlukan persenyawaan untuk menghasilkan telur yang subur.